"A Special Breed": Packing Men and the Class and Racial Politics of Manly Discourses in Post-1945 Edmonton, Alberta - Loch-Drake, Cynthia (Atlantis, 2007)
Edmonton's male packing house workers mobilized rough and respectable notions of masculinity at the bargaining table during the halcyon days of industrial unionism after World War Two. But on the shop floor and in the union hall their attitudes and behaviour could have a corrosive effect that limited worker activism and class solidarity.